2000
DOI: 10.1046/j.1525-1470.2000.01762.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Squaric Acid Dibutylester (SADBE) for Cutaneous Warts in Children

Abstract: We evaluated the efficacy of squaric acid dibutylester (SADBE) contact immunotherapy for the treatment of warts on a series of 188 children. Included in the study were those children who satisfied at least two of the following criteria: single or multiple sites with several warts, warts resistant to repeated medical and/or surgical treatments, recurrent multiple warts, and patient or parent refusal to undergo destructive or surgical treatment. Excluded from the study were children with single warts or with fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 20 publications
3
28
1
1
Order By: Relevance
“…Two series of 29 and 188 mostly pediatric patients sensitized and then treated with SADBE applications demonstrated 69% and 84% clearance rates, respectively (46,47).…”
Section: Squaric Acid and Diphencypronementioning
confidence: 98%
“…Two series of 29 and 188 mostly pediatric patients sensitized and then treated with SADBE applications demonstrated 69% and 84% clearance rates, respectively (46,47).…”
Section: Squaric Acid and Diphencypronementioning
confidence: 98%
“…All plantar warts responded, but statistical analyses to identify whether the wart site was a significant variable was not undertaken. 136 A retrospective review has suggested that topical trichloroacetic acid 50% in combination with SADBE immunotherapy can enhance clearance rates. 137 Side-effects of SADBE and DPC include erythema, desquamation, oedema, pruritus and mild burning.…”
Section: 24b Contact Immunotherapy (Level Of Evidence 2+mentioning
confidence: 99%
“…Combination treatments can be undertaken 10,17,20,21 Other treatments: dithranol, 87 5-FU, 93 formaldehyde, 78 glutaraldehyde, 35 hyperthermia, 55 laser, 58,65 PDT, 68,73 podophyllotoxin, 90 topical immunotherapy 133,136 Plane warts On the backs of the hands or face, plane warts are mainly a cosmetic problem and spontaneous clearance can often be awaited. Destructive and caustic agents are more likely to produce scarring at these sites and should be used with care Salicylic acid cream/ointment 2-10% or cautious use of salicylic acid paint, 12-17%, used without occlusion Cryotherapy, milder freeze Topical retinoid 110,111 Others treatments: acupuncture, 171 cantharidin, 41 for the most part, weak.…”
Section: Future Directionsmentioning
confidence: 99%
“…Since destructive and surgical treatment of warts is painful, especially for children, topical immunotherapy with contact sensitizers is encouraged [1][2]. However, some of these sensitizing compounds such as 2,4-dinitrochlorobenzene are considered as mutagenic [3][4].…”
Section: Introductionmentioning
confidence: 99%